Emergent strategy in higher education: Postmodern digital and the future? - Mohamed Ashmel Mohamed Hashim; Issam Tlemsani; Robin Matthews; Rachel Mason-Jones; Vera Ndrecaj (Administrative Sciences, 2022)
Mintzberg's version of emergent strategy is based on the idea that strategies are contingent on circumstances that change from time to time often very rapidly and therefore papers focused on strategy and detailed planning are limited in their practical application. The word strategy as far as Mintzberg is concerned is anathema, therefore, introducing a concept that has a misconception embedded in it. This paper claims that education for sustainable development and higher education institutions' survival depends on adopting postmodern thinking, in other words, digital transformation. This conceptual paper proposes a blueprint of a process for developing a series of agile potentially short-term conceptual solutions thereby embracing the expectation that the rate of change in societies is accelerating. This paper scrutinizes (a) the applicability of emergent strategy/strategic approach to higher education institutions, (b) how postmodernism influences higher education institutions to become digital hubs of commoditization of knowledge and (c) how the integrated capabilities of digital transformation build sustainability in education delivery. Structural Equation Methodology is proposed to examine the impact of postmodernism on the sustainable delivery of education in higher education institutions, and the need to foster relevant emergent strategies is also justified. The paper also develops new research propositions and managerial implications for driving optimistic digital education. Ultimately, it offers a framework for spear-leading effective and leading post-modernistic digital transformation. Emerging education technology, sustainable digital transformation and advanced use of robotic-human cognitive collaboration are experiencing a significant transformation. Universities play a vital role in enhancing engagement within higher education. One of the managerial implications of the results and discussion is the need for higher education institutions to provide taught leadership and planning in emergent strategy formulation and implementation. The findings confirm the significant importance of linking the Structural Equation Method and the postmodern strategic context in which we argue that higher education institutions require emerging rethinking.
Keywords: 350; DAO and emerging university strategy; digital transformation; postmodernism; sustainability